Early Formation of the Ion‐Conducting Pore in Channelrhodopsin‐21. Issue 16 (23rd December 2014) - Kuhne, Jens; Eisenhauer, Kirstin; Ritter, Eglof; Hegemann, Peter; Gerwert, Klaus; Bartl, Franz
Abstract Channelrhodopsins (ChRs) are light‐gated ion channels that are widely used in optogenetics. They allow precise control of neuronal activity with light, but a detailed understanding of how the channel is gated and the ions are conducted is still lacking. The recent determination of the X‐ray structural model in the closed state marks an important milestone. Herein the open state structure is presented and the early formation of the ion conducting pore is elucidated in atomic detail using time‐resolved FTIR spectroscopy. Photo‐isomerization of the retinal‐chromophore causes a downward movement of the highly conserved E90, which opens the pore. Molecular dynamic (MD) simulations show that water molecules invade through this opened pore, Helix 2 tilts and the channel fully opens within ms. Since E90 is a highly conserved residue, the proposed E90‐Helix2‐tilt (EHT) model might describe a general activation mechanism and provides a new avenue for further mechanistic studies and engineering.